Análisis comparativo de cuentas por cobrar del Comisariato Escolar año 2018,2019 y 2020 - Vicuña Parrales, Milton Manuel (2021)
Correct collection management and credit policies are a vitally important tool in any micro, small or medium-sized company whose vision is to position itself in the market permanently in order to satisfy its clients but above all to avoid liquidity problems. COMISARIATO ESCOLAR is currently one of the largest distributors of stationery and school supplies in the province. As an effect of the pandemic, accounts receivable were affected, reducing their working capital abruptly compared with previous years in the same period of time. A comparative analysis has been carried out to know the percentage fluctuations in accounts receivable in the first semester of 2018, 2019 and 2020. Due to the school season, it is in these months that the highest number of credits are granted in the year with the term of payment based on the closing of the same or according to how the invoice establishes. By not having a department specialized in collections, not keeping a responsible record of the payments made, not knowing in a real way their overdue portfolio of clients, not following credit policies or requesting credit history from clients, there is a decrease in cash of the company, increase in obligations to suppliers, stagnation of inventories and other problems. Through financial reasons of solvency and management, an analysis is carried out to know the situation in which the COMISARIATO ESCOLAR is currently in comparison with other competitors in the commercial sector.